2017
DOI: 10.18280/mmc_b.860305
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Variable Magnetic Field and Convective Boundary Condition on a Stretched 3D Radiative Flow of Cu-H2O Nanofluid

Abstract: The present study is dealt with the influence of a variable magnetic field and thermal radiation on three-dimensional flow of incompressible nanofluid over an exponentially-stretching sheet in association with a convective boundary condition. Patel model is employed in this study because this model contributes more thermal conductivity and hence the heat transfer capability of nanofluids compared to the Maxwell and Brinkman model. In the present analysis, base fluids such as water, 30% ethylene glycol, 50% eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Manjunatha et al 17–19 have extensively discussed linear and nonlinear thermal radiation and observed the importance of radiation parameters in heat transfer enhancement. More studies concerning the radiation were conducted by many researchers and they observed a significant improvement in the rate of heat transfer 20–23 …”
Section: Introductionmentioning
confidence: 99%
“…Manjunatha et al 17–19 have extensively discussed linear and nonlinear thermal radiation and observed the importance of radiation parameters in heat transfer enhancement. More studies concerning the radiation were conducted by many researchers and they observed a significant improvement in the rate of heat transfer 20–23 …”
Section: Introductionmentioning
confidence: 99%
“…Their outcomes disclosed that the Nusselt number diminished with augmented estimations of the radiation parameter. Some inspections regarding the stretching curved surface flow with nonlinear radiation are reported in References [86][87][88][89][90][91][92][93][94][95][96].…”
Section: Introductionmentioning
confidence: 99%
“…The Hall and Joule heating effects on peristaltic flow were studied by Bhatti and Rashidi [15]. Nayak et al [16] studied the influence of variable magnetic field and convective boundary condition on a stretched 3D radiative flow of Cu-H2O nanofluid. Nayak [17] investigated MHD flow and heat transfer on a stretched vertical permeable surface and declared the impact of heat generation/absorption, thermal radiation and chemical reaction there.…”
Section: Introductionmentioning
confidence: 99%